Development status and trend of agricultural robot technology - Jin, Yucheng; Liu, Jizhan; Xu, Zhujie; Yuan, Shouqi; Li, Pingping; Wang, Jizhang (International Journal of Agricultural and Biological Engineering, 2021)
In the face of the contradiction between the increasing demand for agricultural products and the sharp reduction of agricultural resources and labor force, agricultural robot technology is developing explosively on the basis of decades of technical and industrial exploration. In view of the complexity and particularity of the development of agricultural robot technology, it is of great value to summarize its development characteristics and make reasonable judgments on its development trend. In this paper, the type of agricultural robot systems was first discussed. From the classification of agricultural robot systems, the development of main types of monitoring robots, non-selective and selective working robots for crop farming, livestock and poultry farming and aquaculture were introduced in detail. Then the scientific research, core technology and commercialization of different types of agricultural robots were summarized. It is believed that navigation in complex agricultural environments, damage-free robot-crop interaction and agronomy-robot fusion have high scientific value and significance to promote the revolutionary advances in agricultural robot technology. The characteristics of inter-discipline between agricultural robot technology and new materials, artificial intelligence, bionics, agronomy are research focus. The fast damage-free operation, autonomous navigation for complex environments, target detection for complex backgrounds and special design for agricultural robots are considered to be the key technology of agricultural robot development, and the development path is given. Finally, robot-crop interaction simulation, big data support and artificial intelligence are regarded as paths to realize the breakthrough of key agricultural robot technologies. The summary and prospect of this paper are of positive significance to promote the overall development of agricultural robot technology.Keywords: agricultural robot, type, selective, non-selective, trendDOI: 10.25165/j.ijabe.20211404.6821Citation: Jin Y C, Liu J Z, Xu Z J, Yuan S Q, Li P P, Wang J Z. Development status and trend of agricultural robot technology. Int J Agric & Biol Eng, 2021; 14(4): 1–19.